Theoretical framework for user-focused evaluation in office design - Kwon, Minyoung (A+BE | Architecture and the Built Environment, 2020)
As was stated in the introduction, a user-focused renovation approach can enhance user satisfaction in offices and the functional quality of the offices while meeting energy performance goals. The first step for this renovation approach is to identify users’ needs and the physical and psychological factors affecting user satisfaction, as input to office renovation projects. The main aim is to identify the factors that are affecting the physical and psychological satisfaction of users, based on what previous research has found in that field. Therefore, this chapter highlights the main parameters currently applied to the evaluation of user satisfaction, including the definitions based on the literature review. The research approach for the literature review is discussed in section 2.2. Searching was limited to the main key terms of office, work environment, and user satisfaction and comfort. Section 2.3 explores the relationship between office renovation and user satisfaction. The terms user satisfaction and the user’s expectations in workplaces are defined in section 2.4. In section 2.5, the important factors were searched through empirical-based international literature mainly. Based hereupon, section 2.6 discusses the challenge of evaluating user satisfaction. In section 2.7, the findings present ten main parameters to increase user satisfaction in office renovation. The parameters were categorised into three levels based on needs theories to organise the hierarchy of priorities.